Cortical auditory evoked potential assessment on passive speech perception using contrast of voicing and articulation placing among subjects with sensorineural hearing loss / Abdul Rauf Abu Bakar - Abdul Rauf, Abu Bakar (2017)
Hearing ability is one major requirement for human to communicate through language and speech for social interactions. Despite the availability and usage of high technological hearing aid devices, individuals with sensorineural hearing loss (SNHL) reported dissatisfaction. Such displeasures were reported mostly due to intelligibility disruption to the desired signal perception especially in the noisy circumstances, which in turn contribute to device abandonment. The deficiency in the human auditory system on individuals suffering from SNHL is known to be associated with the difficulty in detection of various speech phonologic features that are frequently related to speech perception. In our present development, we evaluate the neurological changes in speech perception difficulties from normal as well people with sensorineural hearing deficit. The main goal of the study is to investigate the impact of speech articulation in place (/ba/ versus /da/) against voicing (/ba/ versus /pa/) contrast using Malay consonant-vowel (CV) speech stimulus towards cortical auditory evoked potential (CAEP) between healthy normal hearing and those suffering from SNHL. CAEPs were tested on 12 right-handed Malaysian male adult subjects (native Malay speakers) having bilateral SNHL and 12 healthy right-handed Malaysian male subjects (native Malay speakers) served as a control group. All volunteers were presented with two sets of Malay CV auditory speech stimuli (/ba/ versus /da/ and /ba/ versus /pa/) delivered at 80 dB sound pressure level (SPL) in an oddball passive paradigm. The two-way repeated measure ANOVAs showed no significant differences in the average CAEP amplitudes and latencies of the responses elicited by the standard and deviant stimuli. P3 was the most detectable CAEPs components appeared significantly in both responses followed by N2, N1, P2 and finally P1. The finding revealed the pattern of CAEPs response recorded at higher activation and longer latency when stimulated by voicing contrast cues compared to position contrast.iv Interestingly, SNHL population elicited greater amplitude with prolonged latencies in the majority of the CAEP components in both speech stimuli. The MMN responses elicited by the SNHL patient were almost half smaller and recorded at longer latencies on both CVs speech stimuli in comparison with that in controls. The assessment of response strength (amplitudes) and response timing (latencies) for the CAEPs indicate the functionality of human brain which may have different processing capabilities depending on the phonological structure of the speech itself and discriminant processing capacity. The existence of different frequency spectral and time-varying acoustic cues of the speech stimuli reflected by the CAEPs response strength and timing recommend that the brain may have an easier task processing in the position contrast compared to voicing stimuli. This finding indirectly provide insight towards CAEP understanding in evaluating passive speech perception of human auditory process to convey better rehabilitation program in the future especially on the difficult to test scenario.